The Roles of Signaling Pathways in Cardiac Regeneration - Valizadeh, Amir; Asghari, Samira; Mansouri, Parinaz; Alemi, Forough; Majidinia, Maryam; Mahmoodpoor, Ata; Yousefi, Bahman (Current Medicinal Chemistry, 2022)
In recent years, knowledge of cardiac regeneration mechanisms has dramatically expanded. Regeneration can replace lost parts of organs, common among animal species. The heart is commonly considered an organ with terminal development, which has no reparability potential during post-natal life. However, some intrinsic regeneration capacity has been reported for cardiac muscle, which opens novel avenues in cardiovascular disease treatment. Different endogenous mechanisms have been studied for cardiac repairing and regeneration in recent decades. Survival, proliferation, inflammation, angiogenesis, cell-cell communication, cardiomyogenesis, and anti-aging pathways are the most important mechanisms that have been studied in this regard. Several in vitro and animal model studies focused on proliferation induction for cardiac regeneration reported promising results. These studies have mainly focused on promoting proliferation signaling pathways and demonstrated various signaling pathways such as Wnt, PI3K/Akt, IGF- 1, TGF-β, Hippo, and VEGF signaling cardiac regeneration. Therefore, in this review, we intend to discuss the connection between different critical signaling pathways in cardiac repair and regeneration.
Keywords: heart